Forecasting market demand using ARIMA and Holt - Winter method: A case study on canned fruit production company - Đạo, Lê Đức; Chi , Phạm Linh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Consumer demand is an important factor in any business, especially in the food retail industry whose products are perishable and have a short life cycle. The daily demand for a food product is affected by external factors, such as seasonality, price reduction and holidays. To satisfy the stochastic demand, product characteristics vary with customer are required to be timely updated based on market dynamicity. According to previous research, to choose suitable forecasting model is the main concern of enterprises on demand management issue. Proper demand forecasting provides organization with valuable information regarding their prospective in their current market, allowing to make appropriated production portfolio. By applying ARIMA and Holt-Winter, this paper aims to forecast the canned fruit demand at a specific company to help them eliminate waste of lean related to production and distribution. Results are evaluated according to forecasting errors (MAD, MSE, MAPE). By comparing the aforementioned methods, it can be concluded that ARIMA outperforms Holt-Winter related to prediction accuracy.